Investigation of Plasma Treatment on Micro-Injection Moulded Microneedle for Drug Delivery - Karthik Nair; Benjamin Whiteside; Colin Grant; Rajnikant Patel; Cristina Tuinea-Bobe; Keith Norris; Anant Paradkar (MDPI AG, 2015)
Plasma technology has been widely used to increase the surface energy of the polymer surfaces for many industrial applications; in particular to increase in wettability. The present work was carried out to investigate how surface modification using plasma treatment modifies the surface energy of micro-injection moulded microneedles and its influence on drug delivery. Microneedles of polyether ether ketone and polycarbonate and have been manufactured using micro-injection moulding and samples from each production batch have been subsequently subjected to a range of plasma treatment. These samples were coated with bovine serum albumin to study the protein adsorption on these treated polymer surfaces. Sample surfaces structures, before and after treatment, were studied using atomic force microscope and surface energies have been obtained using contact angle measurement and calculated using the Owens-Wendt theory. Adsorption performance of bovine serum albumin and release kinetics for each sample set was assessed using a Franz diffusion cell. Results indicate that plasma treatment significantly increases the surface energy and roughness of the microneedles resulting in better adsorption and release of BSA.